2018
DOI: 10.1080/02615479.2018.1553236
|View full text |Cite
|
Sign up to set email alerts
|

Picturing social work, puzzles and passion: exploring and developing transnational professional identities

Abstract: Exploring and in turn developing professional identity is a challenge faced by social work programmes, nationally and internationally. This paper developed from the authors' shared research interest in how social workers and students of social work develop and express their professional identities. We report findings from a workshop designed to explore how a group of social workers from different countries conceptualised social work identity, including the effects of transnational and cultural contexts. Our st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
(34 reference statements)
0
4
0
1
Order By: Relevance
“…Forty-five studies (28%) were concerned with the political, social and healthcare reforms and advances. This included the impact on professional identity (35 or 22%) (Bertin & Pantalone, 2019 ; Blomberg, 2016 ; Bludau, 2017 ; Bochatay, 2018 ; Brunton, 2017 ; Carpenter & Platt, 1997 ; Cascón-Pereira et al, 2016 ; Currie et al, 2010 ; Dahl & Clancy, 2015 ; de Meis et al, 2007 ; Feen-Calligan, 2012 ; Frechette et al, 2020 ; Furtaw, 2004 ; Gent, 2017 ; Gomaa, 1999 ; Handy et al, 2020 ; Hendrikx, 2018 ; Hurley, 2009 ; Iglesias & De Bengoa Vallejo, 2011 ; Kyratsis et al, 2017 ; Larsson et al, 2009 ; McMurray & Pullen, 2008 ; Mishra et al, 2012 ; O’Shea & McGrath, 2019 ; Ocek & Vatansever, 2014 ; Piil et al, 2012 ; Porter & Wilton, 2019 ; Sanders, 2019 ; Snelgrove, 2009 ; Takashima & Saeki, 2019 ; Thompson, 2005 ; Thomson et al, 2014 ; Vincifori & Molinar, 2014 ; Wiles & Vicary, 2019 ; Zufferey, 2012 ), the role of professional identity in adjusting to these reforms or advances (8) (Bertrand, 2009 , 2010 ; Dadich et al, 2015 ; Deppoliti, 2003 ; Franco & Tavares, 2013 ; Gregg & Magilvy, 2001 ; Hammond et al, 2016 ; Wright, 2007 ) as well as the broader impact of political and social reform on recruitment and retention of health care workers through professional identity effects (2) (Allen, 2011 ; Deppoliti, 2008 ).…”
Section: Results (Step 5)mentioning
confidence: 99%
“…Forty-five studies (28%) were concerned with the political, social and healthcare reforms and advances. This included the impact on professional identity (35 or 22%) (Bertin & Pantalone, 2019 ; Blomberg, 2016 ; Bludau, 2017 ; Bochatay, 2018 ; Brunton, 2017 ; Carpenter & Platt, 1997 ; Cascón-Pereira et al, 2016 ; Currie et al, 2010 ; Dahl & Clancy, 2015 ; de Meis et al, 2007 ; Feen-Calligan, 2012 ; Frechette et al, 2020 ; Furtaw, 2004 ; Gent, 2017 ; Gomaa, 1999 ; Handy et al, 2020 ; Hendrikx, 2018 ; Hurley, 2009 ; Iglesias & De Bengoa Vallejo, 2011 ; Kyratsis et al, 2017 ; Larsson et al, 2009 ; McMurray & Pullen, 2008 ; Mishra et al, 2012 ; O’Shea & McGrath, 2019 ; Ocek & Vatansever, 2014 ; Piil et al, 2012 ; Porter & Wilton, 2019 ; Sanders, 2019 ; Snelgrove, 2009 ; Takashima & Saeki, 2019 ; Thompson, 2005 ; Thomson et al, 2014 ; Vincifori & Molinar, 2014 ; Wiles & Vicary, 2019 ; Zufferey, 2012 ), the role of professional identity in adjusting to these reforms or advances (8) (Bertrand, 2009 , 2010 ; Dadich et al, 2015 ; Deppoliti, 2003 ; Franco & Tavares, 2013 ; Gregg & Magilvy, 2001 ; Hammond et al, 2016 ; Wright, 2007 ) as well as the broader impact of political and social reform on recruitment and retention of health care workers through professional identity effects (2) (Allen, 2011 ; Deppoliti, 2008 ).…”
Section: Results (Step 5)mentioning
confidence: 99%
“…For example, one group may complete an RP faster, or include a different level of detail and complexity. In addition, the make-up of a group could impede or foster creativity and exploration, and according to Wiles and Vicary (2019) possibly “over-ride individual views” (p. 59) including willingness to honestly and openly look at the situation.…”
Section: Individually Completed or Group ‘Rich Pictures’mentioning
confidence: 99%
“…The 2017 workshop, developed and delivered with my colleague Sarah Vicary, involved fifteen social workers from Germany, Finland, England, Israel, Australia, the Netherlands and Slovakia. With participants' consent, we recorded, analysed and subsequently published the workshop findings (Wiles and Vicary, 2019). We found that this small group of practitioners shared a collective social work identity, based on a strong commitment to social justice values, which spanned national boundaries.…”
Section: Workhop Findings On Social Workers' Professional Identitymentioning
confidence: 99%
“…At the 2017 European Association of Schools of Social Work (EASSW) conference, I conducted, with my colleague, an interactive workshop exploring how a group of social workers from different countries conceptualised social work identity (Wiles and Vicary, 2019). The main findings were that a shared professional identity, rooted in a strong commitment to social justice values, spans national boundaries.…”
Section: Introductionmentioning
confidence: 99%